The Influence Of Ownership Structure And Company Growth On The Financial Performance Of Manufacturing Companies Listed On The Bei For The 2016 Period - Yofi Syarkani; Tamy Ali Januarty (Journal of Economics and Business (JECOMBI), 2023)
This research is intended to examine the influence of ownership structure and company growth on the financial performance of manufacturing companies listed on the BEI in 2016. Ownership structure is measured through managerial and institutional ownership structures, company growth is measured by changes in asset value. The dependent variable is financial performance, measured through ROA (return on assets). The sampling technique used was purposive sampling. The final number of samples that met the criteria was 110 companies from 144 manufacturing companies registered on the BEI for the 2016 period. The analytical method used was multiple regression analysis. The results of the research show that (1) Ownership structure has a positive effect on the company's financial performance, (2) Company growth has a positive effect on the company's financial performance, (3) Ownership structure and company growth simultaneously have a positive effect on the company's financial performance.